Prebiotic supplementation does not affect reading and cognitive performance in children: A randomised placebo-controlled study. (January 2020) - Capitão, Liliana P; Baião, Rita; Baek, Hee K; Kappelmann, Nils; Sharman, Rachel; Harvey, Christopher-James; Montgomery, Paul; Burnet, Philip WJ
Based on the emerging interest in the effects of gut microbiota on cognition, this proof-of-concept study assessed how children aged 7 to 9 with low reading scores responded to the ingestion of a 3-month prebiotic supplement versus a placebo. As a secondary aim, the effects of the prebiotic on cognition, sleep, behaviour, mood, anxiety, and cortisol were assessed. In this sample, the prebiotic did not affect any of the outcome measures.